General optimization strategy of simulated moving bed units through design of experiments and response surface methodologies - Aniceto, Jose P. S.
The optimization of simulated moving bed (SMB) units is often performed through detailed phenomenological models and require extensive computation time. Hence several optimization methods like the Triangle Theory, and the concept of separation volume have been proposed. However, they do not provide accurate results, when mass transfer limitations are significant, or require a large number of simulations. In this work, a combined Design of Experiments and Response Surface Methodology (DoE-RSM) approach is proposed for SMB optimization, aimed at providing good results with simplicity and reduced number of simulations. The separation of trans-stilbene oxide enantiomers is selected as case study in order to compare DoE-RSM with previous approaches. In the whole, accurate results are obtained with a few number of simulations, allowing for purities above 99.60% for both enantiomers, and productivity of 65.41 kg/(m(adsorbent)(3) day). The versatility of DoE-RSM tool is also discussed, emphasising their advantages and general applicability. (C) 2016 Elsevier Ltd. All rights reserved.